FROM HYPE TO PURCHASE: THE ROLE OF TRENDS, QUALITY, AND SOCIAL MEDIA IN SHAPING CONSUMER INTENTION TOWARD ORTUSEIGHT RUNNING SHOES - Barkhoya, Muhammad Alfin; Putri, Kartika Anggraeni Sudiono (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to examine the influence of trend, product quality, social media marketing, and brand awareness on purchase interest of Ortuseight running shoes among running communities in Malang City. This research employed a quantitative approach with a causal research design. A total of 130 respondents were selected using purposive sampling, consisting of active members of running communities who had purchased Ortuseight shoes. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) through SmartPLS 3.0 software. The findings reveal that all four variables—trend, product quality, social media marketing, and brand awareness—have a significant effect on purchase interest. Among them, brand awareness has the most dominant effect, while social media marketing, although significant, has the smallest impact. These findings highlight the importance of strengthening brand identity and credibility of digital communication to increase consumer purchase interest.